1983
DOI: 10.1108/eb038976
|View full text |Cite
|
Sign up to set email alerts
|

Pims: Fact or Folklore?

Abstract: Perhaps no strategic planning model has generated the controversy that PIMS has. Although some of the critics' charges may be justified, the authors find that the model is still valid and extremely valuable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The PIMS database contains data for many ratio variables but does not contain meaningful absolute data for the components of those ratios, because of the proprietary information they would reveal. Reviewers of the PIMS database (Anderson & Paine, 1978;Lubatkin & Pitts, 1983) have acknowledged the multicollinearity of PIMS variables, but they have not specifically addressed the spuriousness of correlations among PIMS variables because of mathematical artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…The PIMS database contains data for many ratio variables but does not contain meaningful absolute data for the components of those ratios, because of the proprietary information they would reveal. Reviewers of the PIMS database (Anderson & Paine, 1978;Lubatkin & Pitts, 1983) have acknowledged the multicollinearity of PIMS variables, but they have not specifically addressed the spuriousness of correlations among PIMS variables because of mathematical artifacts.…”
Section: Discussionmentioning
confidence: 99%
“…The 1970s saw the widespread adoption of portfolio classification models (Day, 1977) and PIMS analyses of profitability determinants (Lubatkin and Pitts, 1983). US companies such as Mead, General Electric, Borg-Warner and Norton reported success stories as a result of using one or other of such techniques (Cushman, 1978;Loomis, 1980-81).…”
Section: Methods Of Strategy Analysismentioning
confidence: 99%
“…In most previous research, strategic groups have been identified either by inspection (Hunt, 1972;Porter, 1973Porter, , 1979Caves and Porter, 1977;Caves and Pugel, 1980;Harrigan, 1980;Miller, 1981;Oster, 1982;Frazier and Howell, 1983;Lahti, 1983;Lubatkin and Pitts, 1983;Kogut, 1984;Lecraw, 1984;Trembley, 1985;de Bondt, 1988) or by cluster analysis (Hatten and Schendel, 1977;Hatten, Schendel, and Cooper, 1978;Ramsler, 1982;Hayes, Spence, and Marks, 1983;Hergert, 1983;Hawes and Crittenden, 1984;Harrigan, 1985;Amel and Rhoades, 1987;Cool and Schendel, 1987;Fiegenbaum, Sudharshan, and Thomas, 1987;Amel and Rhoades, 1988;Mascarenhas and Aaker, 1989). In addition, other approaches to strategic groups involved analysis of variance (Tassey, 1983;Cool and Shendel, 1988), regressions (Caves, 1984;Primeaux, 1985;Fombrum and Zajac, 1987), chi squares tests (Hatton and Hatton, 1985) and three-mode factor analysis (Baird, Sudharshan, and Thomas, 1988).…”
Section: Previous Research On Strategic Groupsmentioning
confidence: 99%